Composition and Diversity of Macrozoobenthos in Seagrass Areas in Pulau Pahawang Village - Darma Yuliana; Abdullah Aman Damai; Muhamad Gilang Arindra Putra; Rara Diantari; Nur Afni Afrianti; Inggar Damayanti; Yuliana Saleh; David Julian; Muhammad Reza; Berta Putri (The University of Lampung, 2025)
Seagrass beds, particularly those found in Pulau Pahawang Village, serve as vital marine ecosystems that support diverse marine life. This study aims to investigate the composition and diversity of macrozoobenthos within these seagrass ecosystems. Seagrass and macrozoobenthic data were gathered through a 30 m line transect and 1m×1m. The samples were identified to the species or genus level, and the data were analyzed for composition and diversity using the Shannon-Wiener (H’), Dominance (C), and Evenness (E) indices. To assess the relationship between seagrass cover and macrozoobenthic density, a Pearson correlation test was performed. The seagrass species found is Enhalus acoroides. The macrozoobenthic community found in the seagrass ecosystem consists of 2 classes: 22 Gastropoda and 16 Bivalvia. The diversity index of macrozoobenthos (1.47-2.81) show moderate diversity, with high similarity (0.638–0.917), amd low dominance (0.059–0.265) indicates a balance community. The environmental conditions, including water temperature (30.8°C–31.8°C), salinity (30–31), and dissolved oxygen (5.8–6.8 mg/L), strongly support the growth of seagrasses and macrozoobenthos. This study emphasizes the importance of monitoring water quality and species diversity to ensure the sustainability of the seagrass ecosystem and other in Pulau Pahawang Village. Keywords: Biodiversity, Enhalus acoroides, Macrozoobenthos, Seagrass beds, Water quality.